2021
DOI: 10.3390/plants10050929
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of Metal Nanoparticles, a Novel Strategy from Eucalyptus Plants

Abstract: Nanotechnology is a promising tool that has opened the doors of improvement to the quality of human’s lives through its potential in numerous technological aspects. Green chemistry of nanoscale materials (1–100 nm) is as an effective and sustainable strategy to manufacture homogeneous nanoparticles (NPs) with unique properties, thus making the synthesis of green NPs, especially metal nanoparticles (MNPs), the scientist’s core theme. Researchers have tested different organisms to manufacture MNPs and the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 190 publications
0
2
0
Order By: Relevance
“…XRD analysis is a popular technique used to investigate the crystal structure and size of MNP [29]. The XRD patterns of AgNP 50 • C-1:2 were recorded from 20 • to 80 • as shown in Fig.…”
Section: Optimization Of the Biosynthetic Process Of Agnpmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD analysis is a popular technique used to investigate the crystal structure and size of MNP [29]. The XRD patterns of AgNP 50 • C-1:2 were recorded from 20 • to 80 • as shown in Fig.…”
Section: Optimization Of the Biosynthetic Process Of Agnpmentioning
confidence: 99%
“…The features of the MNP generated are known to be influenced by the type of plant extract employed because different plant extracts contain varying quantities of organic reducing agents [28]. Eucalyptus, a genus in the Myrtaceae family, are the world's largest cultivated and natural hardwood flora [29]. Eucalyptus leaves extract has a high content of polyphenols, polyphenols, flavonoids, tannins terpenoids and monoterpenes that contribute to strong reducing ability [30].…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of silver nanoparticles with a UV-Vis spectrophotometer was conducted to observe the characteristic absorption peaks or surface plasmon resonance of the silver particles in the sample using distilled water as a blank solution. Sawalha et al [45] and Razy et al [46] reported that the UV-Vis instrument is an essential instrument to obtain information related to the SPR peaks in silver nanoparticle formation. To complement UV-Vis, nanoparticles can be characterized by EDX, XRD, and FTIR.…”
Section: Characterization Of Silver Nanoparticles Using Uv-vis Spectr...mentioning
confidence: 99%
“…This issue can be overcome by employing biological agents, such as bacteria, fungi, algae, actinomycetes, and plants for the synthesis of metal nanoparticles (John et al 2021 ; Koul et al 2021 ; Chugh et al 2021 ; Rai et al 2021 ; Dikshit et al 2021 ). Recently, the use of plant extracts for nanoparticle synthesis has received much attention due to the rich diversity of phytochemicals, availability in bulk quantities, and simplicity (Balciunaitiene et al 2021 ; Amjad et al 2021 ; Gaddam et al 2021 ; Aboyewa et al 2021 ; Selvakesavan and Franklin 2021 ; Sawalha et al 2021 ; Rajagopal et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%